Measuring Competitiveness in the World's Smallest Economies: Introducing the SSMECI - Ganeshan Wignaraja; David Joiner (Asian Development Bank (ADB), 2004)
"Recent attempts to measure competitiveness across countries have typically neglected the world's smallest economies. Hence, a simple composite index, the small state manufactured export competitiveness index or SSMECI, was developed to benchmark industrial competitiveness. The SSMECI represents the first attempt to provide a comprehensive picture of the competitiveness performance of small states. The performance of small states varies across geographical regions, income groups, and country size classes. Europe was the best performing region, with Malta and Estonia occupying the top two positions in the index. Small states in Southern Africa were the next most successful, with Mauritius and the four Southern African states all in the top 11 of the index. Meanwhile, performance in the Pacific and Western Africa was poor. Statistical analysis of the determinants of competitiveness indicate that high-performing small states had better macroeconomic conditions, higher levels of foreign investment, more trade openness, better levels of education, and modern infrastructure. The paper concludes that a coherent, marketoriented competitiveness strategy in small states is vital to success on international markets."
hdl:11540/1916
Keywords: 330; Internationaler Wettbewerb; Messung; Kleinstaat; Welt